Profile of Critical Thinking Skills in Science Learning Class at Junior High School on Additive Materials - Farida Arifah; Nadi Suprapto; Beni Setiawan (Indonesia Approach Education, 2023)
Critical thinking skills have recently been intensified in learners at all levels of education. Learners are expected to have good critical thinking skills in order to face competition in the world of work. The research conducted was descriptive quantitative with the aim of classifying the critical thinking skills of students. The research subjects were students of class VIII Junior High School in Kediri Regency in the 2022/2023 academic year as many as 20 students. Data collection was conducted through interviews and critical thinking skills tests. The critical thinking skills test instrument includes 5 indicators consisting of 15 multiple choice test items. Analysis was carried out on the test results of students on each indicator and categorised into five critical thinking categories consisting of very high, high, medium, low, and very low. The results showed an average achievement score of 42.08%, interpretation ability 23.47%, analysis ability 50.21%, inference ability 62.31%, evaluation ability 41.10%, and explanation ability 33.33%. Based on these results, it is evident that students' critical thinking skills still need to be trained in order to be improved. Thus, teachers need to implement meaningful science learning in order to improve students' critical thinking skills.